Understanding determinant factors in promoting sustainability of ecosystem: the case of Sabah, Malaysia - Sigang Ung Shio Yien; Nurul Aida Nor Azhar; Nur Syazwana Zabidi; Nurul Syafiqah Ramlee (2021)
This study aims to understand the determinant factors that influence promoting sustainability of ecosystem in Sabah, Malaysia. The nature of the natural ecosystem is self-sustaining and preserving for hundreds to thousands of years the characteristic mosaic of plant forms. However, particular development in Sabah have destroyed the natural ecosystem and had caused an inability to self-sustain the environment. Therefore, protecting natural resources and balance of urban growth within natural surroundings has become the factors to promote sustainability of ecosystem in Sabah, Malaysia. Hence, public participation and collaboration among several parties are significantly essential to sustain the ecosystem of natural environment. Sabah is well-known for its tourism-based resources that encompass the mix of natural environment, people, heritage and culture, tourism facilities, events and nature-based tourism destinations highly exposed to sustainability destruction. However, doing research during the pandemic of COVID-19 limits the data collection to only distributed using Google Form with respondents are those who used to travel to Sabah, including Sabah’s residents between 15 to 64 years old with (n = 384). By using quantitative approaches, this research benefit students and society of Sabah.